Indian Power and Black Power: Reception of the Black Thought in Fausto Reinaga - Cruz, Gustavo R. (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2015)
We present the reception of the “black question” and of several black intellectuals, such as Frantz Fanon, Stokely Carmichael and Charles V. Hamilton, in the works of the indigenous specialist, or Indianista, Fausto Reinaga (1906-1994). is involves a juncture between radical and periphery criticism against the West. Beginning in the rst stage of his reections, the Indianista writer proposes analogies between the indigenous person and the black person, which he vividly relates through several experiences. During the incubation of Indianismo, the second stage of his reections, he produces a prolic response to some of Frantz Fanon’s works. Later, the political consolidation of Reinaga’s Indianismo was accompanied by the ideas of Black Power intellectuals. We reconstruct the process from which arose a short, but important, encounter between indigenous power and black power in the South.